A Study of Universal Severe Acute Respiratory Syndrome Coronavirus 2 RNA Testing Among Residents and Staff in a Large Group of Care Homes in South London. (5th September 2020) - Marossy, Agnes; Rakowicz, Stefan; Bhan, Angela; Noon, Sarah; Rees, Amanda; Virk, Manjinder; Nazafi, Ayazali; Hay, Evie; de Thomasson, Louise; Windle, Christina; Zuckerman, Mark
Abstract: Background: Care homes have experienced a high number of coronavirus disease 2019 (COVID-19)–related deaths among residents since the onset of the pandemic. However, up to May 2020, there has been a lack of information about the extent of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection among residents and staff in care homes and limited testing in this setting. Methods: Combined nose and throat swab testing for SARS-CoV-2 RNA was carried out in 2455 residents and staff across 37 care homes in the London Borough of Bromley across a 3-week period. Results were reported within 24 hours of sample delivery, and data were collected on the presence or absence of symptoms. Results: Overall, the point prevalence of SARS-CoV-2 infection was 6.5%, with a higher rate in residents (9.0%) than in staff (4.7%). A key finding was the high proportion of asymptomatic infection detected in staff (69%) and residents (51%), with evidence of underdetection of symptoms by care home staff. Conclusions: The high proportion of asymptomatic infection combined with underdetection of symptoms by care home staff indicates that offering a test to all residents and staff in care homes with rapid reporting of results would assist accurate identification of infected individuals, facilitating prompt infection prevention and control action. Abstract : The evidence from this study suggests that asymptomatic severe acute respiratory syndrome coronavirus 2 infection is still a significant issue in care home residents and staff, indicating that any testing strategy in this cohort must not be symptom led.